Comparative Study of Flow Patterns around Rhizophora and Avicennia Mangrove Roots Using Computational Fluid Dynamics Simulation. (15th June 2022) - Rahuman, Sini; Ismail, A. Mohamed; Varghese, Shyla Manavalan; Toworfe, George Kwamina
Abstract : The goal of this research is to visualize and compare the patterns of the fluid flow around stilt roots of Rhizophora mangrove species and pneumatophore roots of Avicennia mangrove species in Pichavaram mangrove forest to better understand how mangrove roots can potentially slow down heavy wind flow and thereby offer protection to the coast from natural disasters. The flow around the roots is simulated and analyzed using ANSYS Computational Fluid Dynamics (CFD) software using an unsteady k- ε turbulence model. Wind and water flow velocities vary with respect to time during tsunami, cyclones, typhoons, or hurricanes. Hence, inlet velocity taken as the step function is applied to simulate the change in speed of fluid flow to study the flow behavior. Velocity and pressure are measured at various points around Rhizophora and Avicennia mangrove roots. The findings of the simulation reveal that the Rhizophora stilt roots and pneumatophore roots of Avicennia marina continuously lower the fluid velocity. The Rhizophora mangrove roots can largely decrease the flow velocity because of the complexity and its root dimensions in comparison to Avicennia roots. The data obtained from this research can be applied to increase the efficiency of breakwater models and, as a result, safeguard the shore from natural disasters.